Psychological Burnout Among Raparin University Lectures - Suahm Husein Muhammed; Bakhan Bakhtiyar Muhammadamin; Amin Khdir Ahmad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The present study aimed to identify the level of psychological burnout among Raparin University lectures and to identify the level of psychological burnout according to variables (gender, certification, academic title, and years of experience). The population consisted of lectures from Raparin University, and the sample of the study included (52) lectures from both genders (37) male and (15) female by considering their certification, academic title, and experience. To attain the aims of the study, Christina Maslach's (1982) scale was used. After validity and reliability, the scale was applied to the sample. The data was analyzed using SPSS. The results of the study showed that the level of psychological burnout was low among lecturers. Psychological burnout was higher among males compared to females. And psychological burnout was higher among those who hold master's degrees. And those lecturers whose years of experience are between (6-9) years are suffering more from psychological burnout. At the end of the study, a set of recommendations and suggestions were presented in accordance with the results of the study.